2018
DOI: 10.1063/1.5038859
|View full text |Cite
|
Sign up to set email alerts
|

On the Rayleigh–Kuo criterion for the tertiary instability of zonal flows

Abstract: This paper reports the stability conditions for intense zonal flows (ZFs) and the growth rate γTI of the corresponding "tertiary" instability (TI) within the generalized Hasegawa-Mima plasma model. The analytic calculation extends and revises Kuo's analysis of the mathematically similar barotropic vorticity equation for incompressible neutral fluids on a rotating sphere [H.-L. Kuo, J. Meteor. 6, 105 (1949)]; then, the results are applied to the plasma case. An error in Kuo's original result is pointed out. An… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 48 publications
(118 reference statements)
3
34
0
Order By: Relevance
“…Our derivation makes use of the Weyl calculus, in conjunction with the quasinormal statistical closure and the well-known geometrical-optics assumptions. The obtained model is similar to previous reported works (Parker 2018;Ruiz et al 2016;Zhu et al 2018b;Parker 2016;Zhu et al 2018a) but also includes a nonlinear term describing wave-wave scattering. Unlike in WTT, the collision operator depends on the local ZF velocity and breaks down at the Rayleigh-Kuo threshold.…”
Section: Discussionsupporting
confidence: 87%
“…Our derivation makes use of the Weyl calculus, in conjunction with the quasinormal statistical closure and the well-known geometrical-optics assumptions. The obtained model is similar to previous reported works (Parker 2018;Ruiz et al 2016;Zhu et al 2018b;Parker 2016;Zhu et al 2018a) but also includes a nonlinear term describing wave-wave scattering. Unlike in WTT, the collision operator depends on the local ZF velocity and breaks down at the Rayleigh-Kuo threshold.…”
Section: Discussionsupporting
confidence: 87%
“…(Note that this estimate reinstates the dependence on q, which is absent in M.) Second, the RK criterion does not describe the ZF saturation but rather determines the threshold of the instability of the Kelvin-Helmholtz type that destroys the ZF. (It is also called the 'tertiary instability' by some authors [3,35,36,[55][56][57][58][59], and in our earlier studies we showed that this instability does not exist in the GO limit [35,36,55].) Since the RK threshold corresponds to u>u c,2 (section 3.2), and u u c c ,2 ,1  in the GO regime, we claim that ZFs saturate before the RK threshold is reached.…”
supporting
confidence: 54%
“…They also illustrate the dynamics of test driftons, which are added post hoc. Their trajectories are calculated using the ray equations [55], where the drifton Hamiltonian  is determined by the ZF velocity U that is shown in the lower row and, for test-drifton simulations, treated as a prescribed function of (y, t). In figure 9(a), most driftons are passing and trapped, which leads to ZF oscillations.…”
Section: Numerical Simulations 41 Parameter Scanmentioning
confidence: 99%
“…As shown in Ref. [33], for α → ∞, the KHI is suppressed at all q 2 Z < 1. Here, α is finite but still large (α = 5), so similar conclusions apply.…”
mentioning
confidence: 52%